Viola nujiangensis (Violaceae), a new species of from northwestern Yunnan, China - Chen, Yousheng; Jin, Xiaohua (Phytotaxa, 2015)
A new species of Viola (Violaceae) from northwestern Yunnan, China, namely V. nujiangensis is described and illustrated. It is most similar to V. perpusilla, but differs by its rhizome and root stout, spur ca. 4 mm long, stipules and petiole purplish, and leaf blade glabrous on both surfaces.